2003
DOI: 10.1086/375249
|View full text |Cite
|
Sign up to set email alerts
|

Heritability Analysis of Cytokines as Intermediate Phenotypes of Tuberculosis

Abstract: Numerous studies have provided support for genetic susceptibility to tuberculosis (TB); however, heterogeneity in disease expression has hampered previous genetic studies. The purpose of this work was to investigate possible intermediate phenotypes for TB. A set of cytokine profiles, including antigen-stimulated whole-blood assays for interferon (IFN)-gamma, tumor necrosis factor (TNF)-alpha, transforming growth factor (TGF)-beta, and the ratio of IFN to TNF, were analyzed in 177 pedigrees from a community in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 38 publications
3
48
1
4
Order By: Relevance
“…Our results are in line with published data of TNF-␣ heritabilities with a high degree of genetic determination between 0.6 and 0.8 for TNF-␣ (12,18,19). For IFN-␥ a pedigree study from a community in Uganda with a high prevalence of tuberculosis has reported a heritability of 0.4 (19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with published data of TNF-␣ heritabilities with a high degree of genetic determination between 0.6 and 0.8 for TNF-␣ (12,18,19). For IFN-␥ a pedigree study from a community in Uganda with a high prevalence of tuberculosis has reported a heritability of 0.4 (19).…”
Section: Discussionsupporting
confidence: 92%
“…Heritability of cytokine production has been investigated in a few pedigree studies, including mostly relatives of diseased subjects (12,18,19). Our results are in line with published data of TNF-␣ heritabilities with a high degree of genetic determination between 0.6 and 0.8 for TNF-␣ (12,18,19).…”
Section: Discussionsupporting
confidence: 89%
“…The reasons for ineligibility were as follows: death of one or both twins at or shortly after birth (92), residence outside study area (101) and BCG vaccine given by hospital staff before enrolment (22). Of the 345 eligible pairs, 297 (86%) were enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 345 eligible pairs, 297 (86%) were enrolled. Reasons for nonenrolment were refusal (22) and no traceable address (26). All twin pairs lived together for the duration of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation